Studi Historiografi Buku "Gaddafi’s Harem" Karya Annick Cojean - Ahmad Fajri; Azmi Fitrisia (Galanggang Sejarah, 2019)
This thesis is a study of historiography that discusses the views of Annick Cojean found in Gaddafi Harem towards Muammar Gaddafi in Libya. In conducting this research, historical research methods are the method chosen. The results of this study are how Annick Cojean's views on Muammar Gaddafi in Libya with Cojean use Orientalist, Feminist glasses and also from the perspective of Western Hypocritical Media. There are two parts or phases in the Gaddafi harem book, the first part of the book is Cojean showing a prominent figure in the book called Soraya which tells how the life of the Soraya life from adolescence to the great revolution in Libya in 2011. Part two in the book Cojean focused more on the narrative of Muammar Khadafi's accomplice in carrying out his hegemony for 42 years, until his death in 2011.